Targeting Phospholipase D-mediated Survival Signals in Cancer - Foster, David A. (Current Signal Transduction Therapy, 2006)
An important component of tumor progression is the generation of “survival signals” that suppress default apoptotic programs. Survival signals are ideal targets for anticancer therapeutic strategies because blocking survival signals, in principle, can resurrect the apoptotic signals that are suppressed in cancer cells. Phospholipase D (PLD) activity, which is elevated in a large variety of cancers, generates a survival signal that has been shown to suppress apoptosis in human breast cancer cells. Phosphatidic acid, the metabolic product of PLD activity, contributes to the activation of mTOR (the mammalian target of rapamycin), which has been widely implicated in cancer survival signals. Elevated PLD activity suppresses the tumor suppressors p53, Rb and protein phosphatase 2A, and also causes Myc stabilization - indicating that PLD activity is a key regulator of the cellular machinery that controls cell cycle progression. The ability of PLD to suppress apoptosis makes PLD signal transduction an ideal target for therapeutic intervention in the apparent large number of cancers that have elevated PLD activity. As the era of molecular medicine and pathology evolves, it will be possible to identify individual tumors with elevated PLD activity and target either the signals that activate PLD or the downstream targets of PLD. In this review, the emerging paradigm of PLD survival signals is discussed in the context of therapeutic intervention.
Keywords: mTOR